2015
DOI: 10.1016/j.juro.2014.07.088
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Comparison of Shock Wave Lithotripsy, Retrograde Intrarenal Surgery and Miniperc for Treatment of 1 to 2 cm Radiolucent Lower Calyceal Renal Calculi: A Single Center Experience

Abstract: Miniperc and retrograde intrarenal surgery were more effective than shock wave lithotripsy to treat 1 to 2 cm radiolucent lower calyceal renal calculi in terms of a better stone-free rate, and lesser auxiliary and re-treatment rates. However, miniperc resulted in more complications, greater operative time and radiation exposure, and a longer hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
59
4
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 13 publications
10
59
4
5
Order By: Relevance
“…The SFR data in our study is very consistent with the result of previous studies by Ozturk et al [17] and Kumar et al [18]. Furthermore, we observed that the re-treatment rate for SWL was higher than that of UMP and FURS (p < 0.05).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The SFR data in our study is very consistent with the result of previous studies by Ozturk et al [17] and Kumar et al [18]. Furthermore, we observed that the re-treatment rate for SWL was higher than that of UMP and FURS (p < 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…Kumar et al [18] reported that the complication rate was 6.6% in the SWL group and 11.1% in the FURS group (p = 0.21), with the most common complication being severe pain and urinary tract infection respectively. Bas et al [20] demonstrated that a total of 13.3% cases were affected by complications after FURS with an intraoperative complications rate of 5.9% and a postoperative complication rate of 7.3%, and a further analysis revealed that stone size, stone number, and the presence of congenital renal abnormalities were factors that may affect the complication rate after FURS surgery [20].…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for exclusion: renal stones >2 cm (n = 8), renal stones 1-3 cm (n = 1), and kidney stones 10 mm or less (n = 1). Finally, seven studies [5][6][7][8][9][10][11] were included in the meta-analysis, three RCT [5][6][7] and four CCT [8][9][10][11], published between 2012 and 2014. The literature screening process has been shown in Fig.…”
Section: Study Descriptionmentioning
confidence: 99%
“…Table 1 shows the quality of the included studies as assessed by the methodological quality. Three studies [5][6][7] described the randomization method. None of the studies used an intent-to-treat design and blinded.…”
Section: Study Descriptionmentioning
confidence: 99%
“…On the other hand, Singh et al (22) found that the rate of complete stone-free status was 85.7% for RIRS treatment and 54.3% for ESWL treatment in lower pole stones with sizes between 10 mm and 20 mm and they observed that RIRS was markedly superior. There are other studies that report the superiority of RIRS over ESWL in lower pole stones (23)(24)(25). In an examination of these studies, it was concluded that RIRS is superior to ESWL with respect to providing complete stonefree status as the size of the stone increases; it gives rise to less need for additional intervention; and morbidity rates are higher than in ESWL, but this is not statistically significant.…”
Section: Discussionmentioning
confidence: 99%